PELATIHAN IMPLEMENTASI E-COMMERCE UNTUK MENANGKAP PELUANG USAHA BAGI GENERASI MUDA DI KELURAHAN KUTA - I.K.A. Purnawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Purpose devotion wants to provide knowledge and skills to the younger generation by utilizing e-commercetechnology. The material provided on the application of e-commerce and how to use e-commerce so as toprovide benefits and business opportunities. This dedication was held in Kuta Village to target the youngergeneration. This devotion cooperation with the Lembaga Pemberdayaan Masyarakat Kelurahan Kuta tomaximize the implementation of the training. The method used is to provide training materials through thepresentation, along with the implementation of e-commerce training. The achievement of this devotion is theimplementation of service activities as expected which enthusiastically followed until the end of the event.Participants gain knowledge and skills about the implementation of e-commerce to capture businessopportunities.